PEMANFAATAN POTENSI LOKAL BERUPA SAMPAH KULIT KERANG DAN KULIT UDANG DI KELURAHAN PANGGUNGREJO KOTA PASURUAN - Nurul Akramiah; Yufenti Oktafiah; Sri Hastari (Bajang Institute, 2024)
Panggungrejo Subdistrict, Pasuruan City, has great potential in utilizing the abundant waste from seashells and shrimp shells. This initiative aims to process the waste into high-economic-value products, such as calcium fertilizer, shrimp broth, shrimp-flavored rice crackers, and souvenirs made from seashells. Through a series of training and mentoring sessions, the community is introduced to effective processing techniques, with the hope of improving welfare and raising awareness about environmental sustainability. The results show an increase in the community's knowledge and skills in productively utilizing waste